2018
DOI: 10.1002/jssc.201701461
|View full text |Cite
|
Sign up to set email alerts
|

Determination of organophosphate flame retardants in soil and fish using ultrasound‐assisted extraction, solid‐phase clean‐up, and liquid chromatography with tandem mass spectrometry

Abstract: A solid-liquid extraction method in combination with high-performance liquid chromatography and tandem mass spectrometry was developed and optimized for extraction and analysis of organophosphorus flame retardants in soil and fish. Methanol was chosen as the optimum extraction solvent, not only in terms of extraction efficiency, but also for its broader analyte coverage. The subsequent clean-up by solid-phase extraction is required to eliminate matrix coextractives and reduce matrix effects. Recoveries of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 35 publications
3
9
0
Order By: Relevance
“…14 Lorenzo et al reported concentrations of 9 OPEs at 3.3− 53.0 ng/g in brown trout and European eel from Spain. 15 The most comprehensive study to date was conducted on the levels of 8 OPEs in 12 food groups in Sweden, including cereal, pastries, meat, fish, dairy products, eggs, fats and oils, vegetables, fruits, sugar, and beverages. 16 The results of this study suggested that human exposure through dietary intake is equally important to the ingestion of dust exposure.…”
Section: ■ Introductionmentioning
confidence: 99%
“…14 Lorenzo et al reported concentrations of 9 OPEs at 3.3− 53.0 ng/g in brown trout and European eel from Spain. 15 The most comprehensive study to date was conducted on the levels of 8 OPEs in 12 food groups in Sweden, including cereal, pastries, meat, fish, dairy products, eggs, fats and oils, vegetables, fruits, sugar, and beverages. 16 The results of this study suggested that human exposure through dietary intake is equally important to the ingestion of dust exposure.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This undoubtedly increases the difficulty of subsequent purification and quantitation. Especially for mass spectrometry using electrospray ionization sources, these interfering components can lead to non‐negligible matrix effects .…”
Section: Introductionmentioning
confidence: 99%
“…This undoubtedly increases the difficulty of subsequent purification and quantitation. Especially for mass spectrometry using electrospray ionization sources, these interfering components can lead to nonnegligible matrix effects [18,19]. UPC 2 combines the advantages of SFC and UHPLC with supercritical fluid as the main body of the mobile phase, with higher selectivity and analysis speed than LC, and the polarity range of the analytes it can simultaneously analyze is also larger than that of LC [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Different cartridges have been reported depending on the target compounds, but the common is the HLB (Hydrophilic-Lipophilic-Balanced) [14]. SPE clean-up has been used in methods screening pharmaceuticals [14], personal care product (PCPs) [16], perfluoroalkyl substances (PFASs) [9], organophosphate flame retardants [17] or illicit drugs [18] in biota matrices. This makes SPE a clean-up suitable for multi-residue extraction procedures but sometimes, SPE sorbents fail to eliminate interferences from the matrix.…”
mentioning
confidence: 99%